Long non-coding RNA LOC100507600 functions as a competitive endogenous RNA to regulate BMI1 expression by sponging miR128-1-3p in Hirschsprung's disease. Issue 4 (16th February 2018) - Su, Yang; Wen, Zechao; Shen, Qiyang; Zhang, Hua; Peng, Lei; Chen, Guanglin; Zhu, Zhongxian; Du, Chunxia; Xie, Hua; Li, Hongxing; Xia, Yankai; Tang, Weibing
ABSTRACT: Recently studies reported that long non-coding RNAs (lncRNAs) may take part in a lot of congenital diseases, meanwhile, Hirschsprung's disease (HSCR) is a major congenital digestive tract malformation. Nevertheless whether lncRNAs participate in the occurrence of HSCR and how it contributes to this disease are still unknown. LOC100507600 was selected from our gene expression microarray data obtained from bowel tissues from HSCR patients and negative controls. Subsequently, we used qRT-PCR to prove the result in 64 pairs of HSCR disease bowel stenosis tissues and negative controls. Transwell assay, CCK-8 assay and flow cytometry were employed to explore whether cellular functions change after knocking down the LOC100507600 in SH-SY5Y cell and human 293T cell. Dual-luciferase reporter assay was used to confirm the competitive relationship between BMI1 and LOC100507600 through their association with hsa-miR128–1-3p. Protein extraction and Western blotting were used to further confirm the relationship between LOC100507600 and BMI1. We found that LOC100507600 was obvious reduced in tissues from HSCR patients with noteworthy correlation with BMI1. Furthermore, Downregulation of LOC100507600 repressed cell migration and proliferation and didn't affect cell apoptosis or cycle. Dual-luciferase reporter assay, qRT-PCR and Western blotting assay verified that LOC100507600 serves as a competitive endogenous RNA of miR128–1-3p and down-regulates BMI1 expression by sponging miR128–1-3p in HSCR. In sum, our study researches the potential diagnostic value of LOC100507600 in HSCR and deduces that LOC100507600 can contributes to HSCR as a competitive endogenous RNA to regulate BMI1 expression by sponging miR128–1-3p.